Attenuation of Hypocretin/Orexin Signaling Is Associated With Increased Mortality After Myocardial Infarction - Wohlfahrt, Peter; Jenča, Dominik; Melenovský, Vojtěch; Jarolím, Petr; Dlouhá, Dana; Šramko, Marek; Kotrč, Martin; Želízko, Michael; Mrázková, Jolana; Piťha, Jan; Adámková, Věra; Kautzner, Josef (Journal of the American Heart Association, 2023)
Background The hypocretin/orexin system has been shown to play a role in heart failure. Whether it also influences myocardial infarction (MI) outcomes is unknown. We evaluated the effect of the rs7767652 minor allele T associated with decreased transcription of the hypocretin/orexin receptor-2 and circulating orexin A concentrations on mortality risk after MI. Methods and Results Data from a single-center, prospectively designed registry of consecutive patients hospitalized for MI at a large tertiary cardiology center were analyzed. Patients without previous history of MI or heart failure were included. A random population sample was used to compare allele frequencies in the general population. Out of 1009 patients (aged 64±12 years, 74.6% men) after MI, 6.1% were homozygotes (TT) and 39.4% heterozygotes (CT) for minor allele. Allele frequencies in the MI group did not differ from 1953 subjects from general population (χ2 P=0.62). At index hospitalization, MI size was the same, but ventricular fibrillation and the need for cardiopulmonary resuscitation were more prevalent in the TT allele variant. Among patients with ejection fraction ≤40% at discharge, the TT variant was associated with a lower increase in left ventricular ejection fraction during follow-up (P=0.03). During the 27-month follow-up, there was a statistically significant association of the TT variant with increased mortality risk (hazard ratio [HR], 2.83; P=0.001). Higher circulating orexin A was associated with a lower mortality risk (HR, 0.41; P<0.05). Conclusions Attenuation of hypocretin/orexin signaling is associated with increased mortality risk after MI. This effect may be partially explained by the increased arrhythmic risk and the effect on the left ventricular systolic function recovery.
Keywords: hypocretin/orexin system; Stroke Volume; recovery; Ventricular Function, Left; Male; funkce levé komory srdeční; srdeční selhání; mortality; orexiny; mužské pohlaví; tepový objem; myocardial infarction; infarkt myokardu; outcomes; lidé; ženské pohlaví; Heart Failure; Humans; Myocardial Infarction; inflammation; Orexins; Orexin Receptors; orexinové receptory; Female; hypocretin/orexin receptor‐2